1992
DOI: 10.1016/0266-7681(92)90093-h
|View full text |Cite
|
Sign up to set email alerts
|

Acute Carpal Tunnel Syndrome Due To Pseudogout

Abstract: We report a case of severe fulminating carpal tunnel syndrome secondary to pseudogout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Several cases of carpal tunnel syndrome due to CPPD deposition have been reported. [3][4][5] Researchers found synovitis of the flexor tendon sheaths, in which the tissues were calcified. Taniguchi et al 12 reported CPPD crystal deposition in the elbows of 9 patients with cubital tunnel syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Several cases of carpal tunnel syndrome due to CPPD deposition have been reported. [3][4][5] Researchers found synovitis of the flexor tendon sheaths, in which the tissues were calcified. Taniguchi et al 12 reported CPPD crystal deposition in the elbows of 9 patients with cubital tunnel syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Carpal tunnel syndrome (CTS) with diffuse calcification in the carpal canal has occasionally been reported. In those cases, calcium pyrophosphate dihydrate (CPPD) was the main composition of the calcification [1,13,14], and those cases are better recognized as chondrocalcinosis or pseudogout in the wrist joint. Generally, the diagnosis of CPPD calcification causing CTS is relatively easy to make because a radiograph shows some calcified spots on the floor of the carpal tunnel and polarized light microscopy of the calcified specimen shows rod-like crystals with a weakly positive birefringence [7].…”
Section: Tumorous Calcification Causing Carpal Tunnel Syndromementioning
confidence: 99%
“…Involvement of the knee and hip are emphasized, and wrist involvement has only recently been described (Bensasson et al, 1975; Resnick and Utsinger, 1974; Utsinger et al, 1975). Crystal deposition at the wrist can cause pseudotumours which bulge into the carpal canal (Raimbeau et al, 2001; Rate et al, 1992). The classic feature which is most specific for CPDD is calcification of the triangular fibrocartilage.…”
Section: Historical Perspectivementioning
confidence: 99%